Fabrication of Smart Intercalated Polymer - SMA Nanocomposite - Anjum, Sadaf Saad (Cranfield University, 2015)
Mimicking nature gives rise to many important facets of biomaterials. This study is inspired by nature and reports on the fabrication of an intercalated polymer-NiTi nanocomposite that mimics the structural order of urethral tissue performing micturition. PTFE is chosen due to its hydrophobicity, low surface energy, and thermal and chemical stability. NiTi has been selected as a prime candidate for this research due to its excellent mechanical stability, corrosion resistance, energy absorbance, shape memory and biocompatibility. Nanoscale engineering of intercalated nanocomposites is done by PVD sputtering PTFE and NiTi. FTIR spectroscopy confirms that PTFE reforms as polymer chains after sputtering. Suitable PVD sputtering parameters were selected by investigating their influence on deposition rates, microstructure and properties of PTFE and NiTi thin films. PTFE forms stable nanocomposite coatings with NiTi and displays favourable surface interactions, known as ‘intercalation’. Intercalated PTFE-NiTi films were fabricated as layered and co-sputtered thin films. Co-sputtered nanocomposites contained nearly one-third vacant sites within its internal microstructure because of intercalation while intercalation introduced minute pits in fibrous NiTi columns of layered nanocomposites. These pits allow PTFE to extend their chains and crosslinks, resulting in microstructural and functional changes in the thin films. Intercalated PTFE-NiTi nanocomposites offer a close match to the natural tissue in terms of responding to the fluid contact (wetting angle modifications), and allow the soft and hard matter to incorporate in one framework without any chemical reactions (intercalation). An intercalated microstructure in co-sputtered and layered nanocomposites was verified by EDS-SEM and EDS-TEM techniques. The functional responses were witnessed by changes in water contact angle (WCA) and coefficient of friction (CoF) values measured on the film surface. The WCA (99°) and CoF (0.1 – 0.2) of the intercalated nanocomposite (sample PNT12) were different to the NiTi (top layer). WCA and CoF indicate the internal microstructural interactions because of intercalation.Although the pseudoelastic behaviour of NiTi can provide additional fluid response but the difficulty is an absence of crystallinity in as-deposited NiTi, and the heat treatment that melts PTFE. However, DSC and XRD techniques were employed to find the optimum NiTi composition and transition temperatures for phase transformation related to pseudoelasticity. This study provides the basis to incorporate the shape memory (pseudoelasticity or thermal shape memory effect (shape memory effect)) features of NiTi into the intercalated nanocomposite in future. The intercalated PTFE-NiTi nanocomposite reveals a fascinating research precinct, having the response generating characteristics similar to that of natural tissue.
Keywords: Intercalated nanocomposite; intercalated thin films; PVD magnetron sputtering; thin films; nanocomposites; nanomaterial; PTFE-NiTi; PVD-NiTi; PVD-PTFE; PVD manufacturing parameters